Flow-injection in-line complexation for ion-pair reversed phase high performance liquid chromatography of some metal-4-(2-pyridylazo) resorcinol chelates - Supalax Srijaranai (2018)
Flow injection (FI) was coupled to ion-pair reversed phase high performance liquid chromatography (IP-RPHPLC) for the simultaneous analysis of some metal-4-(2-pyridylazo) resorcinol (PAR) chelates. A simple reverse flow injection (rFI) set-up was used for in-line complexation of metal-PAR chelates prior to their separation by IP-RPHPLC. The rFI conditions were: injection volume of PAR 85 μL, flow rate of metal stream 4.5 mL min-1, concentration of PAR 1.8 × 10-4mol L-1and the mixing coil length of 150 cm. IP-RPHPLC was carried out using a C18μBondapak column with the mobile phase containing 37% acetonitrile, 3.0 mmol L-1acetate buffer pH 6.0 and 6.2 mmol L-1tetrabutylammonium bromide (TBABr) at a flow rate of 1.0 mL min-1and visible detection at 530 and 440 nm. The analysis cycle including in-line complexation and separation by IP-RPHPLC was 16 min, which able to separate Cr(VI) and the PAR chelates of Co(II), Ni(II) and Cu(II). © 2005 Elsevier B.V. All rights reserved.